Pseudoinefficacy: negative feelings from children who cannot be helped reduce warm glow for children who can be helped - Västfjäll, Daniel; Slovic, Paul; Mayorga, Marcus (Frontiers in Psychology, 2015)
In a great many situations where we are asked to aid persons whose lives are endangered, we are not able to help everyone. What are the emotional and motivational consequences of “not helping all”? In a series of experiments, we demonstrate that negative affect arising from children that could not be helped decreases the warm glow of positive feeling associated with aiding the children who can be helped. This demotivation from the children outside of our reach may be a form of “pseudoinefficacy” that is nonrational. We should not be deterred from helping whomever we can because there are others we are not able to help.